Rare retroperitoneal hematoma after percutaneous endoscopic lumbar discectomy: a case report and literature review - Shao, Haiyan; Zhu, Wenhao; Xiong, Xiaochun; Yu, Jie; Fan, Zhaoxiang; Zhou, Chenghong (Frontiers in Surgery, 2025)
BackgroundPercutaneous endoscopic lumbar discectomy (PELD) has emerged as a first-line surgical option for the management of lumbar disc herniation (LDH). However, postoperative complications remain a concern. We present a rare case of retroperitoneal hematoma (RPH) following PELD.Case descriptionA 79-year-old woman who underwent PELD presented with pain in the left inguinal region, lower back, and abdomen, accompanied by hypotension and tachycardia. Abdominal computed tomography (CT) revealed a left-sided RPH. Digital subtraction angiography (DSA) identified a rupture of a left fourth lumbar segmental artery branch. Emergency coil embolization was performed to control the bleeding. Four weeks later, due to the persistence of the hematoma, hematoma evacuation was carried out. Following the procedure, the patient's symptoms resolved, and she experienced relief from discomfort in the left inguinal, lower back, and abdominal regions.ConclusionDSA is critical for diagnosing lumbar arterial bleeding, and arterial embolization is an effective approach to hemostasis. Moreover, a comprehensive understanding of the lumbar intervertebral foraminal space anatomy and enhanced surgical techniques are essential to reduce the risk of retroperitoneal hematoma after PELD. Future studies should focus on optimizing the perioperative management process of PELD to enhance the safety of the procedure.